Combating the Disinfodemic and Spreading Digital Literacy in Indonesia: Analyzing Japelidi's #japelidivshoakscovid19 Campaign - Astuti, Yanti Dwi; Attaymini, Rahmah; Dewi, Maya Sandra Rosita; Zuhri, Achmad (Universitas Ahmad Dahlan, 2023)
The Digital Literacy Activist Network (Japelidi) aims to combat the disinfodemic, increase digital literacy competency, and spread accurate information about COVID-19 through social media campaigns, videos, posters, and an anthology book, with the hope of strengthening the community's immunity against the virus. This study aims to analyze and investigate Japelidi’s action campaign to combat the disinfodemic by using the hashtag #japelidivshoakscovid19 on social media. This study uses the netnographic method to analyze content uploaded on social media to increase engagement rates. Data was collected through online observation methods, interviews, and documentation and analyzed based on various factors such as upload date, number of likes, views, comments, and hashtags. Japelidi launched a campaign called Japelidi vs. Hoaks COVID-19, which included three types of content. These contents provided tips for safe interactions during the pandemic, information in 42 regional languages about caring for oneself and one family, and reliable information about COVID-19. The campaign aimed to provide a sense of belonging, accomplishment, and helpful tips to combat COVID-19. Japelidi's campaign met specific core actions, providing a platform to combat misinformation on social media, a sense of belonging and a sense of accomplishment, and offering tips for healthcare providers. They collaborated internally and externally to create digital content in 42 regional languages, and they should continue campaigning to fight the disinfodemic virus during the ongoing COVID-19 pandemic in Indonesia.